A Meta-Analysis of the Risk Factors of Persistent Pulmonary Hypertension in Newborns - Zhou, Ran; Zheng, You-Ning; Zhang, Xin-Ying; Cheng, Ya-Ying (Frontiers in Pediatrics, 2021)
Objective: To explore the risk factors of persistent pulmonary hypertension of the newborn (PPHN). Methods: By computer-based retrieval and the examination of existing publications, Pubmed, Embase, Cochrane, China Biological Medicine disc, WANFANG, VIP, and CNKI databases were retrieved to find the relevant literature, published on the risk factors of PPHN, for meta-analysis. Two researchers independently screened the literature and extracted data, including the first author，publishing time，time for case collection，volume of samples, and research factors. Quality evaluation of the included literature was conducted by NOS. According to the odds ratio (OR) and 95% confidence interval (CI), the correlations between 12 associated risk factors (7 major risk factors associated with pregnant women: age, BMI index, unipara, pregnancy-induced hypertension syndrome, gestational diabetes mellitus, smoking, and use of some prescription drugs and 5 risk factors associated with newborns: male gender, neonatal asphyxia, gestational weeks < 37, gestational weeks > 42, and cesarean delivery) and PPHN were evaluated. Results: A total of 22 literatures were included in the meta-analysis, which included 7,937 cases in the observation group and 2,613,072 cases in the control group. The top three risk factors for PPHN were women smoking during pregnancy, a gestational age of < 37 weeks, and neonatal asphyxia. The combined OR and 95% CI values were 4.85 (1.98–11.90), 4.34 (1.64–11.50), and 3.90 (2.87–5.31), respectively. Conclusion: This study explored 12 risk factors affecting PPHN, relating to both pregnant women and infants, through meta-analysis and provided references for the early diagnosis of PPHN.